\(\frac{\sqrt{5}-1}{\sqrt{5}+1}+\frac{6}{1-\sqrt{5}}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 7 2020

\(=\frac{\left(\sqrt{5}-1\right)}{\sqrt{5}+1}-\frac{6}{\sqrt{5}-1}=\frac{\left(\sqrt{5}-1\right)^2-6\left(\sqrt{5}+1\right)}{\left(\sqrt{5}+1\right)\left(\sqrt{5}-1\right)}=\)

\(=\frac{5-2\sqrt{5}+1-6\sqrt{5}-6}{5-1}=\frac{-8\sqrt{5}}{4}=-2\sqrt{5}\)

16 tháng 7 2017

\(\frac{6-\sqrt{6}}{\sqrt{6}-1}+\frac{6+\sqrt{6}}{\sqrt{6}}\)\(=\frac{\sqrt{6}\left(\sqrt{6}-1\right)}{\sqrt{6}-1}+\frac{6}{\sqrt{6}}+\frac{\sqrt{6}}{\sqrt{6}}\)\(=\sqrt{6}+\frac{6}{\sqrt{6}}+1\)\(=\sqrt{6}\left(1+\frac{\sqrt{6}}{\sqrt{6}}\right)+1\)\(=\sqrt{6}\left(1+1\right)+1\)\(=\sqrt{6}.2+1\)
\(\frac{\sqrt{10}-\sqrt{2}}{\sqrt{5}-1}+\frac{2-\sqrt{2}}{\sqrt{2}-1}\)\(=\frac{\sqrt{2}\left(\sqrt{5}-1\right)}{\sqrt{5}-1}+\frac{\sqrt{2}\left(\sqrt{2}-1\right)}{\sqrt{2}-1}\)\(=\sqrt{2}+\sqrt{2}=2\sqrt{2}\)
\(\sqrt{\sqrt{5}-\sqrt{3-\sqrt{29-12\sqrt{5}}}}\)\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{20-2.3\sqrt{20}+9}}}\)\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{\left(\sqrt{20}-3\right)^2}}}\)\(=\sqrt{\sqrt{5}-\sqrt{3-I\sqrt{20}-3I}}\)\(=\sqrt{\sqrt{5}-\sqrt{3-\sqrt{20}+3}}\)\(=\sqrt{\sqrt{5}-\sqrt{5-2\sqrt{5}+1}}\)\(=\sqrt{\sqrt{5}-\sqrt{\left(\sqrt{5}-1\right)^2}}\)\(=\sqrt{\sqrt{5}-I\sqrt{5}-1I}\)\(=\sqrt{\sqrt{5}-\sqrt{5}+1}\)\(=\sqrt{1}=1\)

3 tháng 10 2020

a) Ta có: \(\left(\sqrt{8}-3\sqrt{2}+\sqrt{10}\right)\sqrt{2}-\sqrt{5}\)

\(=\left(-\sqrt{2}+\sqrt{10}\right)\sqrt{2}-\sqrt{5}\)

\(=-2+2\sqrt{5}-\sqrt{5}\)

\(=-2+\sqrt{5}\)

3 tháng 10 2020

b) \(\left(\frac{1}{2}\sqrt{\frac{1}{2}}-\frac{3}{2}\sqrt{2}+\frac{4}{5}\sqrt{200}\right)\div\frac{1}{8}\)

\(=\left(\frac{\sqrt{2}}{4}-\frac{3\sqrt{2}}{2}+8\sqrt{2}\right)\cdot8\)

\(=\frac{27\sqrt{2}}{4}\cdot8\)

\(=54\sqrt{2}\)

16 tháng 7 2019

\(A=\frac{1}{\sqrt{3}+1}+\frac{1}{\sqrt{3}-1}\)

\(=\frac{\sqrt{3}-1}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}+\frac{\sqrt{3}+1}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}\)

\(=\frac{\sqrt{3}-1+\sqrt{3}+1}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}\)

\(=\frac{2\sqrt{3}}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}\)

\(=\frac{2\sqrt{3}}{3-1}\)

\(=\frac{2\sqrt{3}}{2}\)

\(=\sqrt{3}\)

\(B=\frac{5+\sqrt{5}}{5-\sqrt{5}}+\frac{5-\sqrt{5}}{5+\sqrt{5}}\)

\(=\frac{\sqrt{5}\left(\sqrt{5}+1\right)}{\sqrt{5}\left(\sqrt{5}-1\right)}+\frac{\sqrt{5}\left(\sqrt{5}-1\right)}{\sqrt{5}\left(\sqrt{5}+1\right)}\)

\(=\frac{\left(\sqrt{5}+1\right)}{\left(\sqrt{5}-1\right)}+\frac{\left(\sqrt{5}-1\right)}{\left(\sqrt{5}+1\right)}\)

\(=\frac{\left(\sqrt{5}+1\right)^2}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}+\frac{\left(\sqrt{5}-1\right)^2}{\left(\sqrt{5}+1\right)\left(\sqrt{5}-1\right)}\)

\(=\frac{5+2\sqrt{5}+1+5-2\sqrt{5}+1}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}\)

\(=\frac{12}{\left(\sqrt{5}-1\right)\left(\sqrt{5}+1\right)}\)

\(=\frac{12}{5-1}\)

\(=\frac{12}{4}\)

\(=3\)

a) \(=\frac{7-4\sqrt{3}+7+4\sqrt{3}}{\left(7+4\sqrt{3}\right)\left(7-4\sqrt{3}\right)}=\frac{14}{49-48}=14\)

b) \(=\frac{15\left(\sqrt{6}-1\right)}{\left(\sqrt{6}+1\right)\left(\sqrt{6}-1\right)}-\frac{5\sqrt{6}}{5}+\frac{4\sqrt{3}-12\sqrt{2}}{\sqrt{6}\left(\sqrt{3}-\sqrt{2}\right)}\)

a) Đặt \(A=\sqrt{5-2\sqrt{6}}+\sqrt{5+2\sqrt{6}}\)

\(A^2=5-2\sqrt{6}+2\sqrt{\left(5-2\sqrt{6}\right)\left(5+2\sqrt{6}\right)}+5+2\sqrt{6}\)

\(=10+2\sqrt{25-4.6}=10+2\sqrt{1}=10+2=12\)

\(\Rightarrow A=\sqrt{12}\)

b)\(\frac{\sqrt{10}-\sqrt{2}}{\sqrt{5}-1}+\frac{2-\sqrt{2}}{\sqrt{2}-1}=\frac{\sqrt{2}.\sqrt{5}-\sqrt{2}}{\sqrt{5}-1}+\frac{\sqrt{2}.\sqrt{2}-\sqrt{2}}{\sqrt{2}-1}\)

\(=\frac{\sqrt{2}\left(\sqrt{5}-1\right)}{\sqrt{5}-1}+\frac{\sqrt{2}\left(\sqrt{2}-1\right)}{\sqrt{2}-1}=\sqrt{2}+\sqrt{2}=2\sqrt{2}\)